Quality of life and barriers to access healthcare services among persons with disability aged 18-59 years in the area of Sarjapur primary health centre: a cross sectional study - Nagaraja, Deepika; Shanbhag, Deepthi N. (International Journal Of Community Medicine And Public Health, 2023)
Background: Disability is defined as any restriction or lack of ability to perform an activity in the manner or within the range considered normal for a human being. Apart from the type and severity of disability, factors such as socioeconomic and marital status are associated with poor QOL life among the PWDs There are distinctive barriers in accessing healthcare services resulting into poorer health outcomes among PWDs. Methods: The objective of the study was to assess the quality of life and barriers associated with access to healthcare services among adults with disabilities in the age group of 18-59 years. This was a cross-sectional descriptive study done in Sarjapur PHC area. The sample size was calculated as 100. Stratified random sampling was used with each village as a strata. WHO BREFQOL was used assess the QOL and a face validated tool was used to assess the barriers in accessing healthcare services Results: Among the 100 PWDs interviewed, 56% were males and 44% were females. The mean age of the study group was 35.5+11.6years. The median (IQR) QOL scores in each domain was as follows: physical 15.1 (12.0, 18.1), psychological 14.0 (10.6, 16.6) social 16.6 (13.3, 18.6) and environmental 16.0 (13.5, 18.0). There was a significant association (p<0.05) between education and QOL, marital status with psychological and environmental domain. The important barriers to access health services were institutional barrier (18%), attitudinal barrier (9%) and environmental barrier (7%). Conclusions: The overall QOL was poor among the study subjects. Institutional barrier was higher when compared attitudinal and environmental barrier.